2017
DOI: 10.2337/dc16-2271
|View full text |Cite
|
Sign up to set email alerts
|

Early Glycemic Control and Magnitude of HbA1c Reduction Predict Cardiovascular Events and Mortality: Population-Based Cohort Study of 24,752 Metformin Initiators

Abstract: A large initial HbA reduction and achievement of low HbA levels within 6 months after metformin initiation are associated with a lower risk of cardiovascular events and death in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 34 publications
0
45
0
1
Order By: Relevance
“…Observational and database studies also provide consistent evidence of a long‐term reduction in CV risk and increased survival for people with type 2 diabetes receiving metformin compared with diet‐only, sulphonylureas, acarbose and insulin . Indeed, patients treated with metformin to achieve glycated haemoglobin (HbA1c) <48 mmol/mol (<6.5%) in their first 6 months of treatment had a lower mortality rate over the following 10 years compared with individuals who did not achieve such early control . This affirms the value of effective early use of metformin to defer CV events years later.…”
Section: Antidiabetic Drugs and CV Effectsmentioning
confidence: 87%
“…Observational and database studies also provide consistent evidence of a long‐term reduction in CV risk and increased survival for people with type 2 diabetes receiving metformin compared with diet‐only, sulphonylureas, acarbose and insulin . Indeed, patients treated with metformin to achieve glycated haemoglobin (HbA1c) <48 mmol/mol (<6.5%) in their first 6 months of treatment had a lower mortality rate over the following 10 years compared with individuals who did not achieve such early control . This affirms the value of effective early use of metformin to defer CV events years later.…”
Section: Antidiabetic Drugs and CV Effectsmentioning
confidence: 87%
“…The so‐called mega‐trials, such as ACCORD, VADT, ADVANCE, etc, did not demonstrate a cardiovascular benefit for intensive vs moderate glycaemic control; however, a large meta‐analyses of these and other studies showed that tight glycaemic control (difference in HbA1c for active comparators vs controls of 0.9%) reduced the relative risk of coronary heart disease events by 15% and of nonfatal myocardial infarction by 17% . An observational study in a cohort of metformin initiators for type 2 diabetes showed that a larger initial fall in HbA1c and maintenance of lower HbA1c levels for the first 6 months of therapy were associated with improved cardiovascular outcomes . Such a benefit may, in principle, apply to any antihyperglycaemic agent, as long as it did not bring side effects deleterious to the cardiovascular system.…”
Section: Cardiovascular Protection With Metforminmentioning
confidence: 99%
“…The ORIGIN trial examined the outcome of low‐dose, basal insulin compared with standard care, and the insulin arm did not reduce either all‐cause mortality or cardiovascular mortality; however, patients in the insulin group received concomitant metformin—shown to markedly attenuate mortality risk in people treated with insulin, in particular at low doses—and insulin was quite frequently used in the standard care arm. In a recent observational study characterizing the outcome of care of those exposed to metformin, where the outcome was major adverse cardiovascular events or all‐cause mortality, there was no evidence of increased adverse outcomes at low HbA1c levels . A further observational study in 2010 reported that there was no difference in all‐cause mortality across the HbA1c range, but this study was subject to immortal time bias and other limitations.…”
Section: Discussionmentioning
confidence: 84%